Pengaruh Literasi Digital Berbantuan Media Televisi Terhadap Perkembangan Sains Anak Usia Dini di RA Al-Munawwarah - Trisya Firdausil Jennah; Nurul Ismaiyah; Hamiduddin Hamiduddin; Nurul Qomariyah Mw; Fina Fitriyah; Prasthy Widhyasmara Putri (Jurnal Raudhah, 2026)
Early childhood science development needs to be stimulated through engaging learning that is concrete, visual, and based on direct experience, thus requiring appropriate media to support conceptual understanding. Digital literacy can help children understand scientific concepts through visual displays, but its utilization is still less than optimal. The purpose of this study was to determine the effect of digital literacy assisted by television media on early childhood science development at RA Al-Munawwarah. This study used a quantitative approach with a pre-experimental model, a one-group pretest-posttest design. The entire group B consisted of 40 children as the population in the study, the research sample amounted to 40 children determined using the total sampling technique. The instrument was an observation sheet. Data analysis used descriptive statistics and the Wilcoxon Signed Rank Test. The results showed an increase in the average value from 51.13 to 72.38, thus having a significant effect. The results of the study are expected to be a reference for educators in utilizing television media as a means of digital literacy.